2008
DOI: 10.1074/jbc.m803019200
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Inhibits Na+/H+ Exchange and HCO3- Absorption through Parallel Phosphatidylinositol 3-Kinase-mTOR and ERK Pathways in Thick Ascending Limb

Abstract: In the medullary thick ascending limb, inhibiting the basolateral NHE1 Na ؉ /H ؉ exchanger with nerve growth factor (NGF) induces actin cytoskeleton remodeling that secondarily inhibits apical NHE3 and transepithelial HCO 3 ؊ absorption. The inhibition by NGF is mediated 50% through activation of extracellular signal-regulated kinase (ERK). Here we examined the signaling pathway responsible for the remainder of the NGF-induced inhibition. Inhibition of HCO 3 ؊ absorption was reduced 45% by the phosphatidylinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(84 citation statements)
references
References 58 publications
4
79
1
Order By: Relevance
“…It has been reported that the serine phosphorylation of IRS-1 at 636/639 is also regulated by the Ser/Thr kinase mammalian target of rapamycin (mTOR) (25), which is activated by TNF-. This cascade seems to exist both dependent and independent of the MEK/ ERK or JNK pathways (26,27). Therefore, AICAR may inhibit the serine phosphorylation of IRS-1 at 636/639 and 307 through the inhibition of mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the serine phosphorylation of IRS-1 at 636/639 is also regulated by the Ser/Thr kinase mammalian target of rapamycin (mTOR) (25), which is activated by TNF-. This cascade seems to exist both dependent and independent of the MEK/ ERK or JNK pathways (26,27). Therefore, AICAR may inhibit the serine phosphorylation of IRS-1 at 636/639 and 307 through the inhibition of mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they observed that the effect of apical LPS on transport was blocked by rapamycin, which inhibits the mTOR/PI3-kinase pathway, whereas the effect of basolateral LPS was blocked by an inhibitor of the ERK pathway. While the authors had previously shown that these pathways inhibit bicarbonate reabsorption and NHE1 and NHE3 activity in thick ascending limbs (7,11), these novel data indicate polarized signaling of the TLR-4 receptor in renal epithelial cells, an important finding in TLR biology not previously described in other cells. In addition, the authors determined that blocking basolateral Na/H exchange with amiloride prevented the inhibitory effect of apical but not basolateral LPS.…”
mentioning
confidence: 75%
“…48 Although the underlying signaling mechanisms are different, HCO 3 − reabsorption through the activation of an extracellular-signal-regulated kinase (ERK)-dependent pathway is decreased in the presence of basolateral LPS. 48,49 In addition, basolateral LPS inhibits HCO 3 − reabsorption in the MTAL through the activation of a TLR4/MyD88/mitogenactivated protein kinase (MEK)/ERK pathway is coupled to the inhibition of sodium-hydrogen exchanger (NHE) 3. NHE3 has been identified as a target of TLR4 signaling in the MTAL.…”
Section: Tlrs and Sepsis-induced Renal Failurementioning
confidence: 99%
“…The TLR2 is expressed selectively in the basolateral membrane of MTAL cells, in contrast to TLR4, which is expressed in both basolateral and apical membrane domains. 49,52 The MTAL HCO 3 − reabsorption is inhibited by bacterial lipopeptides and gram-positive bacterial cell wall structures (lipoteichoic acid and peptidoglycan) recognized by TLR2. Moreover, the inhibition by gram-positive bacterial components is additive to inhibition by basolateral LPS, due to the TLR2 and TLR4 agonists activating different cell signaling pathways.…”
mentioning
confidence: 99%